SUCCESSFUL 28-DAY COMBINATION THERAPY OF MALASSEZIA DERMATITIS IN A 1-YEAR-OLD MIXED SMALL-BREED DOG: A CASE REPORT - Grace Yureka Aurel Siahaan; I Nyoman Suartha; Ida Ayu Dian Kusuma Dewi (Buletin Veteriner Udayana, 2026)
Malasseziosis is a common opportunistic dermatosis in dogs, particularly in tropical environments. Although combination therapy is recommended, evidence from small-breed dogs in Southeast Asian tropical climates remains limited. This case report aims to describe the clinical manifestations, diagnostic approaches, response to combination therapy, and clinical and cytological monitoring in a case of chronic malasseziosis in a small-breed dog. A 1-year-old, 1.95-kg female mixed small-breed dog presented with an 8-month history of bilateral alopecia, scaling, pruritus (PVAS 6/10), and rancid skin odour. Acetate tape impression cytology stained with Diff-Quick confirmed heavy Malassezia colonisation (footprint/snowman morphology). Treatment comprised oral itraconazole (5 mg/kg q24h × 28 days), chlorpheniramine maleate (4 mg/animal q12h), essential fatty acid supplementation, silymarin hepatoprotection, and twice-weekly medicated shampoo (ketoconazole + benzethonium chloride). Cytological monitoring showed a progressive reduction in Malassezia density starting in week 2. By week 4, scaling and abnormal odour had resolved, and hair regrowth was evident in previously alopecic areas. Combination systemic and topical antifungal therapy was effective in resolving malasseziosis within 28 days. Baseline hepatic function testing and scheduled cytological reassessment are recommended to detect recurrence early.